Duplication of the possessive in the Spanish of Amazonian indigenous migrants - Falcón Ccenta, Pedro Manuel (2014)
Description of morphosyntactic characteristics in the double use of possessives in relation with social variables in the Spanish spoken by Amazonian immigrants living in Lima City is offered. Also, a comparative evaluation of codification of grammatical possession is made between Spanish (owned – owner) and the indigenous language (owner – owned). Noting that there are systematic patterns when alternating the canonic construction for the third person (Article + Noun de Noun) and the double use of possession relationships. Moreover, different structures showing double possession are evaluated, showing evidence of influence and social and cultural conditioning as a consequence of the contact between languages.